Pulse Width Modulation Based Decentralized Street LED Light Dimming System - Hussain Attia; Amjad Omar; Maen Takruri; Halah Y. Ali (Institute of Advanced Engineering and Science, 2017)
The high power consumption of conventional street lighting systems, and the consequences on environmental ecosystem due to continuous turning ON of light, have led researchers to seek solutions to this problem. LED light dimming system has been presented in many studies using computerized systems with or without wireless monitoring facility. The demerits of these systems include complexity, high cost and unfixed data transfer speed. This paper proposes to reduce power consumption of street lighting through a decentralized light dimming system that is based on Pulse Width Modulation (PWM). This is in addition to replacing conventional high power lamps with lower power LED lamps. The dimming control circuit of this system is fixed on each pole and controlled individually resulting in faster and more reliable response. The proposed system uses the available infrastructure and is suitable for small or main streets regardless of the number of light poles. It is also flexible in its coverage distance due to the freedom of motion detector selection. The advantages of using LED lighting on the environment as compared to conventional lighting are explained. Simulations reveal the effectiveness of the proposed system on energy saving and on the environment.